Pathology of co-contamination of mycotoxins in poultry farms of Aizawl district of Mizoram - KALITA, JAHNABI J; ARYA, RAHUL S; RAJKHOWA, TRIDIB K; GALI, JAGAN M; SAMANTA, ARUP K (The Indian Journal of Animal Sciences, 2024)
The study was conducted to investigate the naturally occurring pathology of co-contamination of mycotoxins in poultry farms in Aizawl, Mizoram. During the investigation, different chicken farms (n=73) were surveyed for occurrence of disease and mortality. The feed samples collected from affected farms were tested for the presence of aflatoxin, ochratoxin and zearalenone by ELISA kits. The dead birds were subjected to necropsy. Visceral organs from the dead birds were processed for histopathological studies. Fourteen feed samples, out of 49 tested (28.5%) were found affected by co-contamination with aflatoxin, ochratoxin and zearalenone. In this study, the mean level of aflatoxin, ochratoxin and zearalenone was 13.49693 ppb, 4.296286 ppb and 81.74543 ppb, respectively. Clinical signs were ruffled feathers, depression, dullness, huddling, poor growth, anorexia. Necropsy revealed pathological lesions in visceral and lymphoid organs. Histopathological findings were inflammations, degenerative, and necrotic lesions in liver and kidneys. A perusal of available literature did not reveal any study on the presence of co-contamination of Mycotoxicosis in poultry and poultry feed in Aizawl.